EFICIÊNCIA DO CONTROLE MICROBIANO DO GORGULHO-DA-GOIABA EM CAMPO - OLIVEIRA, Isaias; LOUREIRO, Elisângela de Souza; OLIVEIRA, Inessa Steffany Torres de; UCHOA, Manoel Araécio Fernandes; FERNANDES, Marcos Gino; MAESTRE, Marina Rodrigues (ANAIS DO ENIC, 2024)
-